Development and validation of a novel single nucleotide polymorphism (SNP) panel for genetic analysis of Blastomyces spp. and association analysis. Issue 1 (December 2016) - Frost, Holly; Anderson, Jennifer; Ivacic, Lynn; Sloss, Brian; Embil, John; Meece, Jennifer
Abstract Background Single nucleotide polymorphism (SNP) genotyping is increasingly being utilized for molecular typing of pathogens and is cost-effective, especially for large numbers of isolates. The goals of this study were 1) to develop and validate a SNP assay panel for genetic analysis ofBlastomyces spp., 2) ascertain whether microsatellite genotyping and the SNP genotyping with the developed panel resolve identical genetic groups, and 3) explore the utility of SNPs for examining phylogenetic and virulence questions in humans. Methods Three hundred sixty uniqueBlastomyces spp. isolates previously genotyped with microsatellite markers were genotyped with the MassARRAY® SNP genotyping system (Agena Bioscience™, San Diego, CA), for a custom panel of 28 SNPs. Clinical presentation data was analyzed for association with SNP variants. Results Three hundred twenty-threeBlastomyces spp. isolates (90 %) were successfully genotyped by SNP analysis, with results obtained for at least 27 of 28 assays. For 99.7 % of isolates tested by both genotyping methods, microsatellite genetic group assignment correlated with species assignment based on internal transcribed spacer 2 (ITS2) genotyping, with Group 1 (Gr 1) being equivalent toB. gilchristii and Group 2 (Gr 2) being equivalent toB. dermatitidis . Thirteen isolates were genetic hybrids by one or both methods of genotyping and were difficult to assign to a particular genetic group or species. Fifteen SNP loci showed significantly different alleles in cases of pulmonary vs disseminated disease, at ap -value of <0.01 or less. Conclusions This study is the largest genotyping study ofBlastomyces spp . isolates and presents a new method for genetic analysis with which to further explore the relationship between the genetic diversity inBlastomyces spp. and clinical disease presentation. We demonstrated that microsatellite Gr 1 is equivalent toB. gilchristii and Gr 2 is equivalent toB. dermatitidis . We also discovered potential evidence of infrequent recombination between the twoBlastomyces spp. SeveralBlastomyces spp. SNPs were identified as associated with dissemination or pulmonary disease presentation, but additional work is needed to examine virulence SNPs separately withinB. dermatitidis andB. gilchristii .